How Digital Tax Socialization Moderates E-Filling Against Individual Taxpayer Compliance - Malik, Rifki Abdul; Mulyatini, Nurdiana; Akbar, Dendy Syaiful; Rizkia, Tri Septiani (E-Jurnal Akuntansi; Vol 33 No 3 (2023), 2023)
This study aims to analyze the effect of using e-filling on individual taxpayer compliance by including the role of digital tax socialization to strengthen the relationship between the two. The new contribution of this research is to combine literature e-filling, digital tax outreach, and individual taxpayer compliance which were previously examined separately. The primary data for this study came from a questionnaire given to 100 individual taxpayers at KPP Pratama Ciamis. Purposive sampling was used to select the sample for this study. The Partial Least Square method and the SmartPLS tool are used to test the research variables. The results of the study show that e-filling has a positive effect on individual taxpayer compliance. The next result is that digital tax socialization is not significant in strengthening the positive effect of e-filling on individual taxpayer compliance. The practical contribution in this study is by finding that digital tax socialization directly has a positive relationship with individual taxpayer compliance. The results of our study support the commitment of various countries to carry out tax reform in a modern direction. Keywords: E-filling; Digital Tax Socialization; Individual Taxpayer Compliance; Tax Authorities